ISTILAH-ISTILAH MAKANAN DALAM BAHASA INGGRIS DAN BAHASA PASAN (SUATU ANALISIS KONTRASTIF) - SEKEH, JEANNE CAROLINE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research is about â€œThe Terms of Food in English and Pasan Language: A Contrastive Analysisâ€. This research is attempt to identify, analyze, classify and contrasting the terms of food which are used in English and Pasan language. The English data have been collected from text books, dictionaries, and website, whereas the Pasan language data have been elicted from some informants. The descriptive method is used to describe, analyze, classify the kinds of food by using Frischâ€™s concept. After describing the kinds of food in English and Pasan language, the writer contrast both of those languages to find out the similarities and differences by using Ladoâ€™s theory. Theoretically, the significance of this study is to give contribution to the development of language particularly in the field of ethnolinguistics regarding to the terms of food. Particularly, this research will give additional information to the readers about types of food in English and Pasan language. The results show that the kinds of English and Pasan language food terms consist of two groups, they are solid food and beverages/drinks. Solid food consist of fruits, vegetables, bread, meat, fish, and seafood, and cooked food. Beverages/drinks consist of alcoholic drinks and non-alcoholic drinks. But their differences are English food terms (fruit and vegetable) consist of some types, whereas Pasan language food terms (fruits and vegetables) do not. It is expected that this research will help the students to learn food termsÂ  in particular, and to understand the language in general. Keyword: The Terms of Food in English and Pasan Language : A Contrastive Analysis Â